Perancangan Konten Sosial Media Instagram Tari Orek-Orek Ngawi di Sanggar Soeryo Budhoyo untuk Memperkenalkan Warisan Budaya - Masdanur, Fadli; Setiawan, Bayu; Yani, Aditya Rahman (IAI Nasional Laa Roiba Bogor, 2025)
Tari Orek-Orek is a traditional dance from Ngawi Regency that has long been a symbol of local cultural identity. Despite its rich history and cultural significance, the popularity of this dance has declined, especially among the younger generation. One of the factors contributing to this decline is the lack of effective promotion through modern media, particularly digital platforms. This study aims to design an informational media that can introduce Tari Orek-Orek to a wider audience, especially the younger generation, by utilizing technology and social media. A creative and interactive visual approach is employed through digital content, such as promotional videos, and the use of social media features like Instagram to reach a broader audience. It is hoped that this informational media design will help Tari Orek-Orek gain more recognition, appreciation, and preservation as part of Ngawi's cultural heritage. This research is expected to contribute to the preservation of traditional arts and the development of effective promotional media for local performing arts.